2017
DOI: 10.1117/1.oe.56.7.071504
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of turbulence from time-lapse imagery

Abstract: Abstract. Atmospheric turbulence parameters are estimated for an imaging path based on time-lapse imaging results. Atmospheric turbulence causes frame-to-frame shifts of the entire image as well as parts of the image. The statistics of these shifts encode information about the turbulence strength (as characterized by C 2 n , the refractive index structure function constant) along the optical path. The shift variance observed is simply proportional to the variance of the tilt of the optical field averaged over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…This technique was used in Ref. 10 to get an unbiased estimate of r 0 from the motion of image patches of two different sizes. Here it is shown that the weighting functions for differential patch-averaged tilt variances can be used to better reproduce the weighting functions for the spherical wave r 0 and a scintillometer.…”
Section: Creating Arbitrary Weighting Function From Linear Combinatiomentioning
confidence: 99%
See 4 more Smart Citations
“…This technique was used in Ref. 10 to get an unbiased estimate of r 0 from the motion of image patches of two different sizes. Here it is shown that the weighting functions for differential patch-averaged tilt variances can be used to better reproduce the weighting functions for the spherical wave r 0 and a scintillometer.…”
Section: Creating Arbitrary Weighting Function From Linear Combinatiomentioning
confidence: 99%
“…Path-averaged C 2 n was estimated from turbulence-induced random motion of different parts of the building. 9,10 In this work, a scheme to directly estimate turbulence parameters such as pathweighted C 2 n and Fried's coherence diameter r 0 , from the differential motion of target features is described. The differential mode of measurement cancels the effect of any common mode disturbance such as platform vibrations.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations